RNA-seq Gene Profiling Reveals Transcriptional Changes in the Late Phase during Compatible Interaction between a Korean Soybean Cultivar (Glycine max cv. Kwangan) and Pseudomonas syringae pv. syringae B728a - Myoungsub Kim; Dohui Lee; Hyun Suk Cho; Young-Soo Chung; Hee Jin Park; Ho Won Jung (The Plant Pathology Journal, 2022)
Soybean (Glycine max (L) Merr.) provides plant-derived proteins, soy vegetable oils, and various beneficial metabolites to humans and livestock. The importance of soybean is highly underlined, especially when carbon-negative sustainable agriculture is noticeable. However, many diseases by pests and pathogens threaten sustainable soybean production. Therefore, understanding molecular interaction between diverse cultivated varieties and pathogens is essential to developing disease-resistant soybean plants. Here, we established a pathosystem of the Korean domestic cultivar Kwangan against Pseudomonas syringae pv. syringae B728a. This bacterial strain caused apparent disease symptoms and grew well in trifoliate leaves of soybean plants. To examine the disease susceptibility of the cultivar, we analyzed transcriptional changes in soybean leaves on day 5 after P. syringae pv. syringae B728a infection. About 8,900 and 7,780 differentially expressed genes (DEGs) were identified in this study, and significant proportions of DEGs were engaged in various primary and secondary metabolisms. On the other hand, soybean orthologs to well-known plant immune-related genes, especially in plant hormone signal transduction, mitogen-activated protein kinase signaling, and plant-pathogen interaction, were mainly reduced in transcript levels at 5 days post inoculation. These findings present the feature of the compatible interaction between cultivar Kwangan and P. syringae pv. syringae B728a, as a hemibiotroph, at the late infection phase. Collectively, we propose that P. syringae pv. syringae B728a successfully inhibits plant immune response in susceptible plants and deregulates host metabolic processes for their colonization and proliferation, whereas host plants employ diverse metabolites to protect themselves against infection with the hemibiotrophic pathogen at the late infection phase.